Consumption and Income Inequality in Poland During the Economic Transition - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1999)
This paper challenges the conventional wisdom that income inequality in Poland increased substantially following the economic transition in 1989-90. The results, based on micro data from the 1985-92 Household Budget Surveys, indicate that overall income inequality increased during the initial stages of the transition but then declined to pre-transition levels. Consumption distributions reveal a similar pattern. However, earnings inequality did increase markedly after the transition and the relative well-being of different socio-economic groups was altered. Absolute poverty levels increased during the transition, but this increase is attributable to declines in mean income and consumption rather than to changes in inequality.